C2C12 골격근 세포에서 산화적 스트레스에 대한 천심련의 보호 효과 - 성은정(Eunjeong Seong); 최현정(Hyeonjeong Choe); 허희진(Huijin Heo); 이하나(Hana Lee); 김만수(Mansu Kim); 김영화(Younghwa Kim); 정헌상(Heon Sang Jeong); 이준수(Junsoo Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
본 연구는 천심련 추출물의 H2O2로 유도된 산화적 스트레스에 대한 근육세포 보호 효과에 대해 평가하였다. 천심련 추출물은 10 μg/mL의 농도까지 독성이 나타나지 않았으며, H2O2 처리로 감소한 세포 생존율을 농도 의존적으로 증가시켰다. 천심련 추출물은 1, 5 및 10 μg/mL 농도에서 H2O2에 의한 ROS 생성량을 각각 13.1, 14.4 및 17.3% 감소시켜 근육세포에서 H2O2 처리로 인한 산화적 손상으로부터 보호할 수 있음을 확인하였다. 산화적 손상으로부터 보호해주는 항산화 물질인 GSH 함량의 경우, H2O2 처리로 감소한 GSH 함량은 천심련 추출물 처리에 따라 유의적으로 증가하였다. 지질과산화물의 대표적인 물질인 MDA 함량의 경우, H2O2 처리로 증가한 MDA 함량을 천심련 추출물 1, 5 및 10 μg/ mL 농도에서 각각 23.3%, 33.4% 및 54.5% 감소시켰다. 또한 myoblast의 분화된 형태인 myotube에서 H2O2 처리로 근손상 지표인 LDH 및 CK 활성이 증가하였고, 이를 천심련 추출물이 유의적으로 억제하여 근손상을 억제할 수 있음을 확인하였다. 결론적으로 본 연구를 통해 천심련 추출물은 근육세포의 산화적 스트레스를 효과적으로 개선할 수 있는 사코페니아 개선 소재로 활용될 수 있을 것으로 기대된다. The aim of this study was to investigate the protective effect of Andrographis paniculata extract (APE) against H2O2-induced oxidative stress in C2C12 skeletal muscle cells. APE exerted significant dose-dependent protective effect against H2O2-induced cell damage in C2C12 cells without cytotoxicity. The cells treated with APE concentrations of 1, 5, and 10 μg/mL had significantly lower reactive oxygen species (by 13.1%, 14.4%, and 17.3%, respectively) and malondialdehyde levels (by 23.3%, 33.4%, and 54.5%, correspondingly) than H2O2-treated cells. The H2O2 treatment decreased the content of glutathione (GSH), but the treatment with APE neutralized that adverse effect, increasing significantly GSH levels. In addition, we confirmed that H2O2 treatment of myotube cultures increased their lactate dehydrogenase (LDH) and creatine kinase (CK) activities, which are indicators of muscle damage. However, in the experimental myotube cultures, APE treatment significantly inhibited the LDH and CK activities, which were lower than those in the H2O2-treated mypotubes. In conclusion, APE treatment is of considerable significance as a therapy than can improve sarcopenia by attenuating oxidative stress in muscle cells. KCI Citation Count: 0